Notary Authority in Making Auction Minutes as Authentic Deed in the Implementation of Voluntary Auctions - Agung Laksono; Abdul Aziz Nasihuddin; Siti Kunarti (Dinasti Research, 2025)
An auction is a public sale of goods through bidding, requiring the issuance of an auction minutes (auction minutes). These minutes, prepared by an authorized auction official, are authentic deeds with perfect evidentiary strength. The study focuses on the notary's authority to draft auction minutes and their legal validity as authentic evidence in court when acting as an auction official. This research employs a normative juridical method, analyzing the application of legal norms in positive law. Vendu Reglement, PMK No. 213/PMK.06/2020 (updated by PMK No. 122/PMK.06/2023), and PMK No. 189/PMK.06/2017 govern the authority of Class II auction officials. They must meet educational qualifications (minimum bachelor's degree in law or economics), undergo selection, internship, and inauguration. Auction minutes are valid only if prepared by official auction officers, though Article 15(2) of the Notary Law (UUJN) permits notaries to draft them under specific conditions. Article 1868 of the Civil Code mandates that authentic deeds be prepared by authorized officials, granting notaries acting as auction officials the authority to create legally valid auction minutes, provided no evidence disproves their authenticity.